2015
DOI: 10.1016/j.icarus.2014.09.014
|View full text |Cite|
|
Sign up to set email alerts
|

Solar wind implantation into lunar regolith: Hydrogen retention in a surface with defects

Abstract: a b s t r a c t Solar wind protons are implanted directly into the top 100 nm of the lunar near-surface region, but can either quickly diffuse out of the surface or be retained, depending upon surface temperature and the activation energy, U, associated with the implantation site. In this work, we explore the distribution of activation energies upon implantation and the associated hydrogen-retention times; this for comparison with recent observation of OH on the lunar surface. We apply a Monte Carlo approach: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 38 publications
3
80
2
1
Order By: Relevance
“…Emissive surfaces degassed their hydrogen content in less than a lunation, whereas retentive surfaces possessed more high activation energy trapping sites retaining atoms longer than a lunation period. For the intermediate energy range Farrell et al () found that the surface concentration could vary diurnally. However, these previous studies considered the dynamic buildup of the hydrogen surface concentration on timescales much smaller than a lunation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emissive surfaces degassed their hydrogen content in less than a lunation, whereas retentive surfaces possessed more high activation energy trapping sites retaining atoms longer than a lunation period. For the intermediate energy range Farrell et al () found that the surface concentration could vary diurnally. However, these previous studies considered the dynamic buildup of the hydrogen surface concentration on timescales much smaller than a lunation.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of the diffusional lifetime for atoms trapped physically and chemically are given in Table . The lifetimes were evaluated using the τ 1 with D 0 = 10 −6 m 2 /sand h = 100 nm from Farrell et al (). Within crystalline SiO 2 , the energy barrier to vacancy diffusion and H bound in OH groups is ~1–3 eV.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously found [ Farrell et al ., ] that Gaussian‐shaped distributions in activation energy with a progressively lower number of trapped H atoms with increasing activation energy above about 0.4 eV could account for the observations, including modeling the minimum in H retention at noontime locations where solar wind incidence is the greatest. Specifically, at cool temperatures, a large portion of F ( U , T ) remains trapped, but as temperature increases to 400 K, only those few H atoms occupying the high‐energy tail of the distribution on sites with U > 0.5 eV remain, giving rise to an H retention minimum at local noon.…”
Section: Applications Of the H Continuity Equation In Exposed Regolithmentioning
confidence: 97%
“…Past modeling of the H retention in the top tens of nanometers of lunar regolith [ Farrell et al ., ] was designed to find a distribution of activation energy F ( U o , Δ U ) that was consistent with the Chandrayaan‐1 Moon Mineralogy Mapper observations and the complementary IR data sets from Cassini and EPOXI [ Pieters et al ., ; Sunshine et al ., ; Clark , ; McCord et al ., ]. Specifically, these new observations, reported on an OH feature that was of relatively low concentration (mild retention) at 10–1000 ppm [ Clark , ], tended to become more pronounced at large solar zenith angles (near the cooler terminator regions) [ McCord et al ., ], possibly having a diurnal effect [ Sunshine et al ., ] but also possessing a mineralogical component associated with feldpathic mineralogy in highland soils [ McCord et al ., ].…”
Section: Applications Of the H Continuity Equation In Exposed Regolithmentioning
confidence: 99%
See 1 more Smart Citation